Moebius- Poland Syndrome: A case report - Ahmad, Mostapha; Hamdan Rodríguez, Muna; Tovar, Rafael; Neira, Freddy; Arias, Isis; Silvera Redondo, Carlos (Iatreia, 2010)
Moebius syndrome (OMIM 157900) is a congenital disorder related to paralysis of the VI and VII cranial nerves. Clinical findings include mainly facial nerve palsy and strabismus. In addition neurological and musculoskeletal abnormalities are frequently associated. Poland syndrome (OMIM 173800) is another rare congenital abnormality characterized by unilateral absence or hypoplasia of the pectoralis muscle and ipsilateral hand and digit abnormalities. In this work we report an infant with both Moebius and Poland syndromes characteristics. The patient was a male three- month old, who proceeds from the first pregnancy of a healthy couple without consanguinity or inbreeding. The mother referred normal pregnancy course without exposure to teratogens. Physical examination showed brachycephaly, left facial paralysis, blepharoptosis, lack of facial expression, strabismus, lip cornered downwards and micrognathia. Thoracic examination resulted in hypoplastic right pectoral region and inability to palpate the right pectoral muscle. In addition we found ipsilateral hand hypoplasia and oligodactyly of the index, middle, ring and little finger. Finally, bilateral clubfoot was present in inferior limbs. Chest X-ray study showed lack of soft tissue development in the right pectoral region. A cytogenetic study showed normal karyotype. Based on the clinical findings, a Moebius-Poland syndrome diagnosis was made. Moebius síndrome etiology has been related with alteration in the mesoderm and ectoderm levels during embryonic development. However, other studies have proposed a genetic origin (locus 13q12.2) associated to autosomic dominant or recessive inheritance, including cases with recessive inheritance linked to the X chromosome. Nowadays, a vascular origin associated to teratogenic agents such as Misoprostol derivatives drugs have increased the Moebius clinical frequency. Although, there is a commonly well accepted vascular theory associated to Moebius, Poland and Klippel-Feil syndromes. In this case study, neither family history nor teratogen exposure were found. This case was classified as a sporadic vascular originated defects and family counseling was offered. Keywords: Moebius, Poland, syndrome, facial palsy. Muscle hypoplasia.